PELATIHAN PEMBUATAN MEDIA TANAM ORGANIK SERTA STRATEGI PEMASARAN DIGITAL UNTUK KEMANDIRIAN MITRA ORGANIK JAYA DI KABUPATEN PADANG PARIAMAN - Ratna Aisuwarya; Afriyanti Dwi Kartika; Sinta Silvia; Monika Rianti Helmi (LPPM Universitas Andalas, 2023)
This engagement reports the outcomes of a series of training activities conducted to significantly contribute to the development of sustainable agricultural practices in collaboration with our partner, Organik Jaya, located in Padang Pariaman Regency. These training activities encompass various facets with a focus on enhancing the participants' capacity and knowledge. Firstly, we provided training on the technique of composting organic fertilizers from animal waste. Participants were educated on the management of agricultural and livestock waste to produce high-quality organic fertilizers, which can enhance soil fertility and reduce the use of environmentally hazardous chemical fertilizers. Subsequently, we conducted training on the assembly of efficient organic fertilizer grinding machines. Additionally, we offered training in the technique of wood and husk charcoal production using the Drumkiln method based on reverse airflow. This has a positive impact on converting agrikulturlah and forest waste into high-value products like charcoal. Furthermore, we offered strategic guidance on marketing products through online Marketplace platforms, assisting our partners in reaching a wider market and increasing their income. The primary objective of these training sessions was to augment the knowledge and skills of the participants in implementing sustainable practices relevant to agriculture and the environment. The results of these activities are expected to yield positive benefits for local agriculture and provide fresh insights into managing organic raw materials and modern marketing strategies. This engagement provides a crucial foundation for advancing agriculture that is more sustainable and adaptable in facing future challenges.